PERBEDAAN KADAR PLASMA ENDOTELIN-1 PADA WANITA PENGIDAP DIABETES MELLITUS TIPE 2 DENGAN DISLIPIDEMIA DAN TANPA DISLIPIDEMIA (TINJAUAN PUSTAKA DAN LAPORAN PENELITIAN) - , ALBERTINUS F. DAELI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background. Diabetes Mellitus is associated with an increased risk of atherosclerosis, and coronary artery disease is a major cause of death in patients with diabetes. Dyslipidemia is also a major risk factor for coronary artery disease. Endothelial dysfunction may precede the development of atherosclerosis from this conditions. Endothelial markers endothelin-1 (ET-1) were assessed in patients type 2 Diabetes Mellitus women with dyslipidemia and without dyslipidemia Aim. To evaluate the difference plasma levels of endothelin-1 in type 2 diabetes mellitus women with dyslipidemia and without dyslipidemia. Methods. Cross sectional design was conducted on subjects from outpatients type 2 diabetes mellitus women with dyslipidemia and without dyslipidemia at endocrinology clinic, Dr. Sardjito General Hospital, Yogyakarta. ELISA sandwichâs methods was used to measure plasma levels of endothelin-1 from veins blood. Differences between groups were compared by studentâs unpaired ttest and Mann-Whitney test. Results. Among 60 subjects, there are 30 with dyslipidemia (50%) and 30 without dyslipidemia (50%). Median age were 55 (44-59) years old. Plasma levels of endothelin-1 seemed higher in type 2 diabetes mellitus women with dyslipidemia than without dyslipidemia although they were not statistically significant (18,94 Â± 9,72 ng/ml vs. 15,2 Â± 7,91 ng/ml, p=0,108). Conclusion. The plasma levels of endothelin-1 has no significant different between type 2 diabetes mellitus women with dyslipidemia and without dyslipidemia.